SĄŽININGUMAS BRAZILIJOS CIVILINIAME KODEKSE: PO DEŠIMTIES METŲ - Tomasevicius, E. (Teisė, 2013)
The general clause of good faith was one of the innovations of the Brazilian Civil Code, enacted in 2002. It came into force in January 2003, in order to widespread ethics in private affairs. Indeed, good faith was applied in specific cases, such as the “theory of appearance” or the requirement of utmost good faith in insurance contracts. But in the Civil Code of 2002, heavily influenced by German, Italian and Portuguese codes, good faith is applied to provide operability, ethicity and sociality in private relations as well as in the enforcement of private law by courts. In this sense, good faith has been used to impose duties of consistency, information and cooperation between the parties of a transaction. The aim of this paper was to introduce an overview of good faith, its consecration in the Brazilian Civil Code and then to analyze its application in Brazilian Courts in the last ten years.